Experimental and Analytical Study on the Longitudinal Shear Bond Behaviour of Basalt Textile-Reinforced Concrete Composite Slab - Aniket Shirgaonkar; Yogesh Patil (Journal of Rehabilitation in Civil Engineering)
Composite deck slab flooring system is gaining popularity since they allow for simpler, lightweight, and more cost-effective building construction technique. The main constituent materials of a composite slab are profiled deck steel sheet and concrete. Profiled steel sheet serves two purposes: it acts as a main reinforcing structural element as well as a permanent formwork during the construction phase. The efficiency of the composite slab mainly depends upon the shear interaction between concrete and steel decking sheet. This paper contributes to improving the horizontal shear strength of composite slab by utilizing basalt textile reinforced concrete (BTRC) topping. The current research is focused on examining the behavior of this shear bond action and improving its performance even without the shear connectors. Three types of concrete topping and four different shear spans (250 mm, 325 mm, 550 mm, and 625 mm) are the variables of the testing. Based on the load-displacement response, failure mechanisms, maximum strain recorded in concrete/steel, load-slip characteristics, steel-concrete shear bond resistance, and the structural performances of basalt textile-reinforced concrete (BTRC) composite slabs were compared with the conventional concrete (CC) composite slabs. BTRC composite slabs are found to be more ductile than the conventional concrete composite slab, with increased load-bearing and slip resisting capacity. Both the m–k and partial shear connection (PSC) approaches were used to calculate the horizontal shear strength of the composite floor. The m-k technique has proven to be more meticulous than the PSC method.